Factors driving mobile network operator profitability in public safety mobile broadband projects - Savunen, Tapio; Töyli, Juuso; Kekolahti, Pekka; Mähönen, Petri (Elsevier, 2026)
This study examines the business aspects of mobile network operators (MNOs) in public safety communications projects using MNOs' 4G/5G networks. It analyses key factors affecting MNO profitability in public safety broadband projects, including business models, network investments, public funding, contract length, and business risks. A discounted cash flow model was used, supported by sensitivity analyses, reflecting national public safety projects in the United States and Europe. Based on public data and expert interviews, the model shows that significant public funding is essential for MNO profitability. The single-actor business model used in the United States has been shown to be more profitable than the multi-actor model used in European projects due to its broader service portfolio. Additionally, the findings illustrate how public safety projects can influence MNOs’ standard mobile business by affecting market share, with substantial implications for revenue. This study provides a financial model and recommendations to help MNOs maximise profitability in public safety projects and offers strategic guidance for government authorities in designing effective public safety procurement processes. It also presents policy recommendations to further assist with regulation.